Relationship between Growth and Development with Nutritional Status Profile of Children Aged 0-5 Years - Wolly Candramila; Erna Cristina Pasaribu; Asriah Nurdini Mardiyyaningsih; Desriani Lestari (JURNAL INFO KESEHATAN, 2025)
Stunting remains a major concern in Indonesia, particularly in Jungkat Village, where early detection is crucial for mitigating its impact on child growth and development. While the Pre-Screening Development Questionnaire (KPSP) is commonly used to assess child development, its relationship with nutritional status remains unclear. This study is aimed to determine the nutritional status, KPSP category, and the relationship between these variables in children aged 0-5 years in Jungkat Village. A cross-sectional quantitative study was conducted from June to August 2023 in Jungkat Village, Mempawah Regency. Ethical approval was obtained from the Health Research Ethics Committee, Faculty of Medicine, Tanjungpura University. A total of 400 children aged 0 to 5 years and 11 months were selected using participatory sampling. Height, weight, and KPSP scores were measured following standardized guidelines, and nutritional status was categorized based on height-for-age, weight-for-age, and BMI-for-age indices. Ordinal logistic regression was performed using R to analyze the relationship between nutritional status and KPSP scores. The prevalence of stunting was 36.3% (10.5% severely stunted, 25.8% stunted), while 5.2% had very low weight and 19.2% were underweight. BMI analysis showed 80% had values within the normal range, while 2.2% were overweight, 0.2% obese, and 2.4% severely wasted. In terms of child development, 77.75% exhibited normal development, 19.75% required reassessment, and 2.5% showed developmental deviations. However, no significant correlation was found between nutritional status and KPSP scores (p > 0.05). These findings suggest that factors beyond nutritional status, such as environmental conditions and parenting practices, may have a greater influence on child development. Thus, national nutritional standards should be adapted to local ecological and genetic characteristics to improve the effectiveness of nutritional and health interventions. Further research integrating socio-environmental factors is recommended to gain a more comprehensive understanding of child development determinants.